Analisis Sistem Antrian dalam Penggunaan E-Toll untuk Menentukan Jumlah Gardu Optimal pada Gerbang Tol - Puji Dwi Wahyuni; Merita Bernik (University of Merdeka Malang, 2020)
Considering the function of the toll road is to provide optimal services without any obstacles that can reduce the flow of vehicles, toll road providers or operators must strive for existing facilities to work optimally. Based on that, this study aims to indicate the number of optimum toll gates that should be operated to be able to control congestion and reduce the number of vehicles waiting in Pasteur 2 Toll Gate. Pasteur 2 Toll Gate is a toll gate with the heaviest volume of vehicles incorporated in the Purbaleunyi Toll Road. This toll gate is the entrance door for tourists who want to enter the city of Bandung. Vehicle volume density occurs during rush hour every day without exception at weekends, which results in the queue of vehicles. This study used a descriptive survey method by analyzing the queuing system after e-toll was implemented. Data collection is done through interviews and observations that are carried out every weekend within one month. This research was conducted to determine the optimal number of substations to be able to reduce the density that occurred. The results of this study indicate that the number of optimum substations that should be operated to be able to control congestion and reduce the number of vehicles waiting and being in the system or in smaller queues is 11 toll gates.https://doi.org/10.26905/jmdk.v8i2.4598